Implementasi Nilai-Nilai Kepemimpinan Di Pondok Pesantren Modern Nurussalam Kabupaten Karawang - Siti Masruroh; Andewi Suhartini; Nurwajah Ahmad EQ (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The purpose of the mini-research on the Implementation of Leadership Values ​​at the Modern Nuruslam Islamic Boarding School, Karawang Regency, is to find out the process of leadership regeneration in the management of Islamic boarding schools, namely by holding Basic Student Leadership Training (LDKS) activities as an agenda that must be followed by all students of the Nuruslam Islamic Boarding School in Karawang Regency. With the Basic Santri Leadership Training program, as a means to explore the potential of students in developing leadership. Santri have the skills to become a leader/leader when plunged in the midst of society. Santri will be familiar with the activities carried out in Islamic boarding schools. The writing method is a qualitative method with data collection through interviews with ustadz and students of modern Nurusalam Islamic boarding schools, Karawang district.Keywords: Implementation, Modern Islamic Boarding School. LDKS